Climate change adaptation in seaweed aquaculture: A survey of farmer knowledge and practices - Arwati, Sitti; Nadja, Rahmawaty Andi; Mahyuddin, Mahyuddin; Heliawaty, Heliawaty (Edelweiss Applied Science and Technology, 2025)
This study aimed to assess the knowledge level of seaweed farmers regarding climate change and adaptation practices against climate change impacts in Takalar District, South Sulawesi. Data were collected using the quantitative survey method, comprising observations, interviews, and questionnaires with 178 respondents. Approximately 37.64% of the farmers had a rudimentary understanding of climate change, but their insight was limited. However, over 70% perceived its risks and effects, and 64.05% had heard of seasonal changes. For adaptation, 80.34% engaged in early harvesting upon the appearance of disease symptoms, while 77.53% performed crop monitoring twice a day. More than 60% adapted planting schedules and spacing in relation to climate. More than 50% adopted superior seeds and different cultivation methods. These outcomes highlight the ways in which seaweed farmers are already responding to climate challenges and serve as important information for designing stronger forms of adaptation. Such adaptive behaviors can help mitigate possible losses and build resilience in the seaweed farming community. The findings should also help inform climate adaptation efforts in similar coastal communities around the world and contribute to broader discussions about how to sustain agricultural practices in a changing climate.